KEPEMIMPINAN KEPALA DESA DALAM PENYELENGARAAN PEMERINTAHAN DESA BIDANG PEMBANGUNAN DI DESA PULAU BARU KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI TAHUN 2013 - Erlianto, Refli; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Success or failure of most organizations is determined by the quality leader entrusted with the task of leading organisasi.because that, in moving the indispensable participation of leadership and quality (quality leader).However, in fact in the village of Pulau Baru Kuantan District Hilir Regency Kuantan Singingi Opposite leadership The village head was found indications less acceptable to all the villagers are: (1) the high cost of obtaining a birth certificate that is not in accordance with Regulation Kuantan Singingi About Retribution Identity Card replacement fee and Deed civil registration. (2) Development conducted in the village of Pulau Baru through funding from the Village Fund Allocation (ADD) is less well targeted. (3) The head of the village are less able to embrace and accommodate the aspirations of the community so that leadership is less able to integrate the interests in the midst of society. (4) The head of the village are less able to establish cooperation with the Village Consultative Body as a partner in rural development.The method used is qualitative data collection techniques with interviews, was conducted to determine the leadership of the village chief in the administration of the village administration, literature study, a method of data collection in order to obtain secondary data hold directly on the object under study.Based on the results of the study authors, leadership village chief in the village of Pulau Baru Kuantan District Hilir Regency Kuantan Singingi Opposite is the village chief has not been able to embrace the public to be together in rural development. Various ways have been made head of the village community is not biased invite voluntarily engaged in rural development. And the constraints faced by the village chief in the lack of leadership is the approach taken in the village chief invited as well as to direct the development and the lack of communication with the village head of the village, and the lack of coordination with the village chief BPD as its partners in the development and accommodate the aspirations of the villagers.Keywords: Leadership Village Head